LAS APTITUDES Y ACTITUDES EMPRESARIALES DE LOS ESTUDIANTES DE ADMINISTRACIÓN EN LAS UNIVERSIDADES PÚBLICAS DE LIMA - CALLAO - Espinoza Herrera, Nemesio (2004)
The objective of thís research paper is to know the causes and characterístícs of professional unemployment in Perú as well as the current educational strategies in use in management departments of public universities and the aftermath of the entrepreneurial attitudes and aptitu des of management undergraduate students and theír incidence in the employment level. Method: The fieldwork on this research has been undertaken in the management departments of three public universitíes in the cities of Lima and Callao by havíng students of diverse ages, study years, and study shifts, filling adhoc questionnaires. Results: li has been observed as with decades ago the permanence of the same educational strategies oriented towardsforming undergraduate professionals in management aspiring to occupy management positions in large and medium size enterprises, and as it is impossible right noto, by ali means, they integrate a great group of unemployed professíonal managers. There are neíther educational strategies oriented towards educating entrepteneurs nor to promote entrepreneurial aptitudes and attitudes. Conclusions: In order to invert this Peruvian national reality, it demands the urgent necessity of educational paradigm changes in the undergraduate management departments of public universities in order to be more geared towards the education of entrepreneurs and the systematic deployment of entrepreneurial attitudes and aptitudes on the students during their professional education.